1999
DOI: 10.1098/rspb.1999.0910
|View full text |Cite
|
Sign up to set email alerts
|

Languages, geography and HLA haplotypes in Native American and Asian populations

Abstract: A number of studies based on linguistic, dental and genetic data have proposed that the colonization of the New World took place in three separate waves of migration from North-East Asia. Recently, other studies have suggested that only one major migration occurred. It is the aim of this study to assess these opposing migration hypotheses using molecular-typed HLA class II alleles to compare the relationships between linguistic and genetic data in contemporary Native American populations. Our results suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This finding may indicate that the modern genetic analogue, the Pima, was not representative of the older morphological sample from Grand Gulch, Utah. Alternatively, the marked genetic differentiation of the Pima sample may be the result of the extreme bottle-necking hypothesized to have occurred during the migration of early Americans to the New World (Szathmary, 1993;Santos et al, 1995;Monsalve et al, 1999;Bortolini et al, 2002;Battilana et al, 2006). While neutral molecular markers may drift unchecked, the cranium is likely to be under some degree of stabilizing selection.…”
Section: Discussionmentioning
confidence: 91%
“…This finding may indicate that the modern genetic analogue, the Pima, was not representative of the older morphological sample from Grand Gulch, Utah. Alternatively, the marked genetic differentiation of the Pima sample may be the result of the extreme bottle-necking hypothesized to have occurred during the migration of early Americans to the New World (Szathmary, 1993;Santos et al, 1995;Monsalve et al, 1999;Bortolini et al, 2002;Battilana et al, 2006). While neutral molecular markers may drift unchecked, the cranium is likely to be under some degree of stabilizing selection.…”
Section: Discussionmentioning
confidence: 91%
“…Genetic distance is a measure of overall evolutionary divergence between two populations. It usually correlates with the historical, geographical and linguistic relationships (14–16) although there are examples of the lack of congruence between linguistic and genetic data in some populations (17, 18). Despite being under strong selective pressure, HLA genes have been successfully used in genetic distance studies (19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…These exceptions appear to correspond to either rare cases of language replacement or genetic admixture between two linguistically distinct populations (Cavalli-Sforza 1997; Chu et al 1998) or cases in which the underlying classi¢cation of language variation remains uncertain (Ward et al 1993;Monsalve et al 1999). Thus, there appears to be a real di¡erence between humans and birds in the degree of coevolution of genetic and cultural traits.…”
Section: Discussionmentioning
confidence: 99%
“…For traditional human societies there is mounting evidence that language variation is often highly correlated with variation in neutral genes, suggesting that transmission of language has been primarily vertical (i.e. from parents to o¡spring) Piazza et al 1995;Cavalli-Sforza 1997) although some exceptions have been noted (Ward et al 1993;Chu et al 1998;Monsalve et al 1999). Conversely, studies of male song in oscine songbirds have generally not found a strong association between vocal and genetic variation (Kroodsma et al 1985;Fleischer & Rothstein 1988;Payne & Westneat 1988;Lougheed & Handford 1992;Catchpole & Slater 1995) suggesting that horizontal or oblique transmission (i.e.…”
Section: Introductionmentioning
confidence: 99%